Kolaborasi Orang Tua dan Guru dalam Pengembangan Sosial Emosional Anak Usia Dini - Parera, Siti Fatimah; Supriadi, Supriadi (STAI Bumi Silampari, 2025)
Collaboration between parents and teachers is essential in early childhood social-emotional development. However, a need to better understand ways to improve this collaboration to support children's holistic development remains. Purpose of the article: This article aims to explore practical strategies that can be used to increase collaboration between parents and teachers in the social-emotional development of early childhood. This qualitative research uses a literature review to gather information about strategies that have been proven effective in increasing parent-teacher collaboration. Data were analyzed descriptively to identify relevant patterns and findings. The research results show that several methods can be used to improve collaboration between parents and teachers, including establishing open and regular communication, developing parent involvement, building trust and partnerships, providing resources and support, and setting shared goals. Implementing these strategies can help create a supportive, inclusive, and holistic learning environment for young children's social-emotional development.